Cation‐Vacancy Ordered Superstructure Enhanced Cycling Stability in Tungsten Bronze Anode. Issue 36 (24th July 2022) - Xiong, Xuhui; Yang, Liting; Liang, Guisheng; Liu, Zhengwang; Yang, Ziqi; Zhang, Ruixuan; Wang, Chao; Che, Renchao
Abstract: Niobium‐based tungsten bronze oxides have recently emerged as attractive fast‐charging anodes for lithium‐ion batteries (LIBs), owing to their structural openings and adjustability. However, electrodes with tungsten bronze structures usually suffer from structural variability induced by Li + intercalation/de‐intercalation, leading to unsatisfactory cycling performance. To circumvent this limitation, a novel tetragonal tungsten bronze (TTB) structure, Ba3.4 Nb10 O28.4 (BNO), is developed as an anode material for LIBs with prominent cycling performance. An unprecedented cation‐vacancy ordered superstructure with a periodic distribution of active and inactive sites is revealed inside the BNO. Through multiple characterizations and theoretical studies, it is demonstrated that this superstructure can improve the lithium‐ion diffusion and disperse the structural strain induced by Li + ‐intercalation to enable stable Li + ‐storage. Benefiting from the superstructure‐induced local structural stability, both the BNO bulk and Ba3.4 Nb10 O28.4 @C (BNO@C) microspheres can deliver >90% capacity retention after 250 cycles at 2 C and close to 90% capacity retention after 2000 cycles at 10 C. These results are of significant importance for establishing the structure–property relationship between the cation‐vacancy ordered superstructure and Li + ‐storage performance, facilitating the rational design of stable tungsten bronze anodes. Abstract : A novel tetragonal tungsten bronze Ba3.4 Nb10 O28.4 (BNO) is prepared as a potential anode for lithium‐ion batteries, which possesses significantly superior cycling durability compared to other tungsten bronze anodes. The enhanced cycling performance can be explained by an unprecedented cation‐vacancy ordered superstructure in BNO, which facilitates lithium‐ion transport and enables local structural stability.